Extreme Programming Untuk Perancangan Sistem E-Commerce Berbasis Web - Rahmi Imanda; Hastin Estrika (STMIK Budi Darma, 2023)
Several companies still use books as media for sales, ordering, and data collection of material stocks in today's technology-filled world. The media in this book may be lost, torn, or wet, preventing data from being saved. This research aims to build an e-commerce system for easy and fast selling and ordering of goods, enabling data collection of material stocks, and providing additional features for employee attendance management. The method used for designing this e-commerce system is Extreme Programming (XP). Starting from the stages of system planning, design, coding, and testing. The object of this research was conducted on business owners of Gunung Kidul Young Coconut Fuel, with test results of 95.30% of 25 people who use the e-commerce system to make buying and selling transactions easier so that they become more systematic